Design of a tooth-shaped magnetorheological brake with multiple coils - Bien, Nguyen Van; Zy Zy, Le Hai; Nguyen, Quoc Hung; Nguyen, Ngoc Diep; Duyen, Do Qui (Vietnam Journal of Mechanics, 2024)
This research presents an optimized design for a tooth-shaped magnetorheological brake (MRB) with multiple coils. The MRB configuration consists of a disk immersed in magnetorheological fluid (MRF), where four coils act as electromagnets when an electric current is applied. The energized coils induce the alignment of suspended particles in the MRF, forming a chain-like structure that increases the fluid's viscosity. This rapid, strong, and controllable phenomenon enables the MRB to find applications in haptic systems, tension control, and industrial braking systems. To analyze the electromagnetic behavior of the brake, Finite Element Method (FEM) simulations are conducted using ANSYS APDL, and the optimization process is performed utilizing ANSYS Workbench software. The software provides optimized geometries for the brake, resulting in significant improvements in desired performance aspects compared to prior designs, etc.